2005
DOI: 10.1038/ni1172
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 regulates the self-renewal capacity and differentiation of human memory B cells and controls Bcl-6 expression

Abstract: It is unknown how B cells that mature during a germinal center reaction 'decide' between plasma or memory cell fate. Here we describe a previously unknown subpopulation of B cells in the human germinal center that is characterized by tyrosine phosphorylated transcriptional activator STAT5. These cells had an activated centrocyte phenotype and had abundant expression of BCL6 but low expression of PRDM1, both encoding transcriptional repression proteins. Using RNA interference and ectopic expression of constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
166
4
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(181 citation statements)
references
References 49 publications
10
166
4
1
Order By: Relevance
“…Recently, it has been demonstrated that STAT5 upregulates BCL6 in a subset of germinal center cells (Scheeren et al, 2005). Using reporter assays, it was demonstrated that the STAT5-binding site was located at À526 to À534 according to the þ 1 nucleotide defined by Ohashi et al (1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that STAT5 upregulates BCL6 in a subset of germinal center cells (Scheeren et al, 2005). Using reporter assays, it was demonstrated that the STAT5-binding site was located at À526 to À534 according to the þ 1 nucleotide defined by Ohashi et al (1995).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we utilized this site in our ChIP experiments as the control region (Figure 6a), and in NKL cells stimulated with IL-2, STAT5 does not bind to that site (Figure 6c). It is possible that the site identified by Scheeren et al (2005) is a STAT5-binding site specific to germinal center cells in which STAT5 upregulates BCL6 expression. Therefore, STAT5 may be upregulating BCL6 in some cell types and downregulating BCL6 expression in other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of cytokines stimulation and antigendriven BCR activity may drive specific B-cell fate in the germinal center. There, STAT5 may play a special role in the self-renewal of B cells (Scheeren et al, 2005). The delayed activation of STAT after BCR engagement could be secondary to interleukin (IL)-6 or CD40L production, because neutralizing antibodies to IL-6 or CD40 inhibited STAT3 activation following BCR engagement (Fan and Rothstein, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a subpopulation of germinal center B cells that is characterized by pSTAT5 expression with an activated centrocyte phenotype has been identified recently. 31 Nuclear expression of pSTAT5 was detected in all megakaryocytes of myeloproliferative disorders with high JAK2 mutated/wild-type ratios, in all nuclei of the K562 pellets, and in erythroid precursors of myeloid disorders without JAK2 mutations (Figure 2d and e).…”
Section: Immunohistochemistrymentioning
confidence: 92%